Mission to Mars: a computer science curriculum for middle school STEM camps - Feldhausen, Russell A. (Kansas State University, 2018)
This thesis presents a curriculum designed for 5th and 6th grade students attending a summer camp for science, technology, engineering, and mathematics (STEM) disciplines. The curriculum uses several concepts from educational theory and computer science education research. It also uses techniques such as cognitive apprenticeship, expansive framing, and scaffolded lessons to increase student learning outcomes. It was taught during two cohorts of a STEM summer camp. The curriculum is analyzed through self-efficacy surveys both before and after the class, measuring how students judged their own capability to use skills learned during the class. Analysis of the data shows that the increase in student self-efficacy has a medium to large effect size overall, as well as student self-efficacy with many computational thinking skills. Data from various population groups based on gender, previous STEM experience, and socio-economic status indicators is also analyzed. Finally, many areas of future work and improvement are presented and discussed. The outcome of this work is to demonstrate the effectiveness of the curriculum presented in increasing student self-efficacy with computational thinking skills, specifically by showing the links between content in the curriculum and specific computational thinking skills.
Keywords: Computer science curriculum; STEM camp; Self efficacy; Computational thinking; Cognitive apprenticeship